Comparison of Diorama and Animation Media in Enhancing Cognitive Learning Outcomes on Ecosystem Material for Fifth-Grade Students: A Quasi-Experimental Study at SDN 1 Pataruman - Raisha Fauziyah Azzahra; Abdul latip; Irfan Hilman (Universitas Garut, 2025)
This study aimed to analyze the impact utilizing diorama and animation media in on the topic of “Harmony in the Ecosystem” for fifth-grade elementary students. employed a quantitative approach with an experimental method, involving two classes as samples: the experimental class used diorama media (n=24) and the control class used animation media (n=21). Data were collected through pretests and posttests, then analyzed using normality tests, the Mann-Whitney U test, and N-Gain calculations with SPSS version 20. The results showed that the implementation of learning with both media was optimal, as evidenced by 100% achievement in observation checklists., although the N-Gain for diorama (0.20) was slightly higher than for animation (0.14), both categorized as low. In conclusion, diorama and animation media have relatively equal effectiveness in supporting students’ conceptual understanding, with media selection adjusted according to the material characteristics and students’ needs.